Multinationals as flagship firms regional business networks - Rugman, Alan M.; D'Cruz, Joseph R. (Oxford University Press, 2000)
Alan Rugman and Joseph D'Cruz bridge the literature on networks and multinationals by introducing the concept of the flagship firm. This theory of the flagship firm/five partners model is then applied to the telecommunications, chemicals, automotive and electronics sectors.